Fundamentals of selling - Futrell, Charles (McGraw-Hill, 2006)
Includes bibliographical references (pages 603-607) and index.; Fundamentals of Selling, 13e trains readers on a detailed, yet broad, step-by-step selling process that is universal in nature. Numerous sales personnel in the industry today have commented on how this market-leading textbook reflects what they do on sales calls with prospects and customers. The goal of Fundamentals of Selling has always been to demonstrate to students the order of steps within the selling process; provide numerous examples of what should be in each step; and show how the steps within the selling process interact with one another. Combined with up-to-date content and a strong ethical focus, the 13th edition of Fundamentals of Selling teaches sales the way a mentor would: with a strong, practical focus that puts the customer first; "Welcome to the Thirteenth Edition of Fundamentals of Selling A megatrend in today's business world involves going to extreme efforts to meet consumer needs. Organizations cannot afford to lose customers. It is always easier to sell to a satisfied customer than an unsatisfied one. The cost of acquiring a new customer is higher than keeping a present customer